DEVELOPING MAGIC ROUND TO TEACH INTERROGATIVE SENTENCES - Tri Agustini Solihati; Lystiana Nurhayat Hakim (University of Kuningan, 2019)
Vocabulary mastery and sentence structure are often considered to be the most challenging things in mastering English. Besides, both teacher and students are often bored on how they are explained and understood. Thus, keeping students’ motivation in learning vocabulary and sentence structure needs more effort as it should be more than just teachers’ attendance and explanation. Choosing a proper teaching media can be one of the solutions. This research aims to produce Magic Round as one of the choices for teaching interrogative sentences. It was developed through Research and Development (RD) by implementing several steps, including preliminary studies, research planning, product design, product validation, product trial, and producing final product. Validity was assessed by both technological and material experts. Those reached 90% and 92%. The usefulness and feasibility were taken by the user and observer. Those gained 91% and 91%. In conclusion, this media is quiet appropriate to be used in teaching English interrogative sentences.